2002
DOI: 10.1097/00001813-200208000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Raltitrexed plus oxaliplatin as first-line chemotherapy in metastatic colorectal carcinoma: a multicentric phase II trial

Abstract: For advanced colorectal carcinoma, two new drugs, raltitrexed (TOM) and oxaliplatin (L-OHP), have recently shown interesting results. Preclinical and clinical studies suggest that this combination, because of its favorable toxicity profile, high response rate and convenient schedule of administration, can be administered successfully in this disease. In our phase II study, 37 non pre-treated patients with metastatic colorectal carcinoma were treated with TOM (3 mg/m(2)) and L-OHP (130 mg/m(2)) every 3 weeks. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 20 publications
1
7
2
Order By: Relevance
“…In contrast with previous favorable reports on the combination of raltitrexed plus oxaliplatin in first-line treatment of advanced CRC [5,6,7,8], the results of the present study with raltitrexed plus CPT-11 show a suboptimal response rate and a limited median overall patient survival that arises the question of its actual efficacy. These figures also compare unfavorably with the more standard combinations of 5-FU plus CPT-11 [1, 22] or 5-FU plus oxaliplatin [2].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast with previous favorable reports on the combination of raltitrexed plus oxaliplatin in first-line treatment of advanced CRC [5,6,7,8], the results of the present study with raltitrexed plus CPT-11 show a suboptimal response rate and a limited median overall patient survival that arises the question of its actual efficacy. These figures also compare unfavorably with the more standard combinations of 5-FU plus CPT-11 [1, 22] or 5-FU plus oxaliplatin [2].…”
Section: Discussioncontrasting
confidence: 99%
“…However, raltitrexed combinations have already been explored in this context. In phase II trials, raltitrexed plus oxaliplatin has shown a consistent activity in patients with previously untreated, advanced CRC (43–54% response rate) [5,6,7,8]. Preclinical data suggest a synergistic activity between CPT-11 and raltitrexed and three recent phase I studies have shown that single-agent full doses of both drugs can be safely given thrice-weekly [9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the predefined eligibility criteria, we selected 12 studies [3][4][5][7][8][9][10][11][12][13][14][15] that fulfilled the qualitative and quantitative requirements of the systematic analysis. A total of 735 patients were enrolled across the selected trials (range, 37-94).…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent phase II studies have attempted to define the activity of raltitrexed in combination with other agents in colorectal cancer. One of the most active doublets is an oxaliplatin combination, and in 6 separate studies (Table 14 [219][220][221][222][223][224]), response rates of between 43 and 62% were obtained in a frontline setting. Activity drops to between 16 and 33% in previously treated patients (Table 15 […”
Section: Raltitrexedmentioning
confidence: 99%